2021
DOI: 10.1029/2021ea001901
|View full text |Cite
|
Sign up to set email alerts
|

Five‐Year Analysis of Evaposublimation Characteristics and Its Role on Surface Energy Balance SEB on a Midlatitude Continental Glacier

Abstract: As a crucial component of cryosphere, the glacier has been considered as an excellent indicator of climate change (Fernandez & Mark, 2016;GTOS, 2008;Oerlemans & Reichert, 2000). With special thermodynamic and hydrological characteristics, the glacier' sublimation play a significant role in exchange process of water and heat between the cryosphere and atmosphere, and thus can be the important factor in regional, even global water and energy balances, as well as the atmospheric circulation (De'ry & Yau, 2002;Suz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Both had high seasonal variabilities with the largest absolutes in spring (Figure 6a). This was related to the relatively more snowfalls (high albedo) and fewer cloud covers during the spring of this glacier (Guo et al., 2021). However, the monthly mean of net shortwave radiation S in summer reached to 82 W m −2 , which was much larger than other seasons.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Both had high seasonal variabilities with the largest absolutes in spring (Figure 6a). This was related to the relatively more snowfalls (high albedo) and fewer cloud covers during the spring of this glacier (Guo et al., 2021). However, the monthly mean of net shortwave radiation S in summer reached to 82 W m −2 , which was much larger than other seasons.…”
Section: Resultsmentioning
confidence: 98%
“…The energy and mass balances of the glaciers in Qilian Mountains are bound to be profoundly affected by the seasonal variation in westerlies. Studies revealed that the surface sublimation on the TP glaciers is more intense during the dry or non‐melt period with dry air and strong winds (e.g., Guo et al., 2021; Li et al., 2018; Liu et al., 2021). Therefore, the westerlies may also be the most crucial driver of sublimation by affecting the main meteorological factors on the August‐one glacier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, winds were more moderate and quite weak over summer (mean u = 3.5 m s −1 ), with a minimum average of 3.3 m s −1 in August. In addition, wind speed is found to be higher during the daytime than during night (Guo et al., 2021). Figure 2b showed that the west wind direction prevailed over the study glacier, while the mean wind direction WD was significantly lower during summer than that of other seasons.…”
Section: Resultsmentioning
confidence: 99%
“…Under the influence of Indian monsoon, the glacier sublimation/evaporation was relatively small, and ablation was controlled by melting, which can provide a large amount of water resources for rivers, while when the glacier weather was dominated by westerlies (more arid and windy), the glacier mass loss was dominated by sublimation (Wang et al., 2019). Sublimation has been identified to be important for the mass loss of TP glaciers during winter due to the arid and windy weather conditions, and can have a great influence on glacier accumulation (e.g., Guo et al., 2021; Mandal et al., 2022; Stigter et al., 2018). For the glaciers on the northern TP (controlled by westerlies all year round), glacier mass losses due to sublimation or evaposublimation have been found to be responsible for 29% of the annual precipitation on the Laohugou glacier (Sun, 2012) and to be 14.5% on the August‐one glacier (Guo et al., 2021).…”
Section: Introductionmentioning
confidence: 99%